The 'culture of two': Communication accommodation in ravens' (Corvus corax) nonvocal signaling. Issue 1 (2nd January 2020) - Luef, Eva Maria; Ter Maat, Andries; Jäger, Manuela; Pika, Simone
Abstract: The theory of communication accommodation refers to linguistic processes through which human interactants—consciously or subconsciously—shift their speech and gesture styles to resemble those of their conversation partners. This phenomenon represents a crucial feature of human language and is particularly pronounced in affiliative and/or strong relationships. Communication accommodation is suggested to reflect a need for social integration or identification with other individuals and, as such, plays an important role in communication within closely-knit social units and in particular monogamous relationships. Concerning nonhuman animals, the phenomenon of communication accommodation has received relatively little research attention. Here, we tested whether common ravens ( Corvus corax ), which are known for their sophisticated communicative skills and lifelong monogamous pair bonds, accommodate their nonvocal signals within a relationship (i.e., pair-partners). Specifically, we investigated whether the nonvocal signals exchanged within pairs become synchronized over time. Our results provided evidence that raven pairs matched their repertoires, with recipients reciprocating the signals of their communication partners in relation to time spent together. This study thus strengthens the hypothesis that the motives to form and maintain affiliate relationships may have been crucial in boosting not only cognitive but also communicative abilities, and provides insight into the role social bonding might have played in the evolution of communicative plasticity.